Vanadium-bearing magnetite and ilmenite mineralization and beneficiation from the Sinarsuk V- Ti project, West Greenland - T. Grammatikopoulos; A. McKen; O. Christiansen (Canadian Institute of Mining, Metallurgy and Petroleum, 2002)
Vanadium mineralization occurs in oxide-rich horizons within layered metagabbro zones of the Sinarsuk deposit, West Greenland. The main oxide minerals are vanadiferous magnetite and ilmenite, comprising 30% to 90% of the rock volume and the ratio of magnetite to ilmenite ranges from 3:2 to 4:1. Ore microscopy shows that magnetite and ilmenite vary between 0.2 mm and 4.5 mm in grain size, but locally they are coarser grained. Grains are subhedral to euhedral and annealed suggesting that they will liberate very well upon grinding. Electron microprobe analyses indicate that magnetite grains are homogeneous and have a vanadium content, in different mineralized samples, ranging from 1.93 wt% to 2.68 wt% equivalent V2O5. Ilmenite hosts abundant and variably sized hematite lamellae, and it has vanadium contents ranging from 0.32 wt% to 0.59 wt% equivalent V2O5. Preliminary beneficiation of two composite bulk samples shows the samples can be beneficiated fairly easily using low-intensity magnetic separation at a coarse grind (106 microns to 600 microns) to yield a vanadiferous magnetite concentrate. The presence of hematite lamellae in ilmenite prevents recovery of a satisfactory ilmenite concentrate. The most likely beneficiation flowsheet would encompass a primary mill (SAG or rod mill), which would grind to about 600 microns, followed by a rougher magnetic separation stage. The rougher magnetic concentrate would be reground in a ball mill until suitable liberation is achieved. The reground material would then be cleaned in further LIMS stages. However, further laboratory testing is required to establish the final beneficiation program. This work demonstrates the value of mineralogical investigation in guiding and explaining the results of beneficiation processes.